CRISPR-based m6A modification and its potential applications in telomerase regulation - Yi, Mingliang; Wang, Mingyue; Xu, Yongjie; Cao, Zhikun; Ling, Yinghui; Zhang, Zijun; Cao, Hongguo (Frontiers in Cell and Developmental Biology, 2023)
Telomerase determines cell lifespan by controlling chromosome stability and cell viability, m6A epigenetic modification plays an important role in the regulation of telomerase activity. Using CRISPR epigenome editing to analyze specific m6A modification sites in telomerase will provide an important tool for analyzing the molecular mechanism of m6A modification regulating telomerase activity. In this review, we clarified the relevant applications of CRISPR system, paid special attention to the regulation of m6A modification in stem cells and cancer cells based on CRISPR system, emphasized the regulation of m6A modification on telomerase activity, pointed out that m6A modification sites regulate telomerase activity, and discussed strategies based on telomerase activity and disease treatment, which are helpful to promote the research of anti-aging and tumor related diseases.